Desmoplastic small round cell tumour in a 74 year old man: an uncommon cause of ascites (case report) - Prebtani Ally PH; Heikkila Andrew J (BMC, 2011)
Abstract A rare case is provided of a 74 year old man who presented with ascites of unknown etiology. CT scan of the abdomen revealed extensive omental caking, and omental biopsy cytogenetics showed findings in keeping with a diagnosis of desmoplastic small round cell tumour (DSRCT). This case is unique in that it involves a significantly older patient, negative WT1 immunohistochemical staining, and negative cytology. Despite repeated paracenteses and fluid management, the patient died in hospital secondary to renal complications.